2011
DOI: 10.1299/jpes.5.218
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production Using an Ethanol-Steam-Reforming Reactor with Cu/ZnO/Al2O3 and Ru/Al2O3 Catalysts

Abstract: In the present study, we examine the dominant chemical reactions and the optimal conditions, assuming the design of ethanol-steam-reforming reactors. Experiments are performed for two catalysts, Cu/ZnO/Al 2 O 3 and Ru/Al 2 O 3 . Using a household-use-scale reactor with well-controlled temperature distributions, we compare experimental results with chemical-equilibrium theories. As a result, the Cu/ZnO/Al 2 O 3 catalyst shows rather high performance at low-reaction-temperature T, which suggests that the Cu/ZnO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
2
0
6
Order By: Relevance
“…(1)- (6) しかし,実用改質器設計の際に必要となる実機スケー ルの改質器については,あまり詳細に調べられていない.そこで,著者らは,これまでに,設計規範確立の為の 基礎研究を実施してきた. (7), (8) すなわち,実用的大きさを有する改質器を用い,効率的改質の為の種々の最適反応 条件を調べてきた.その結果,低反応温度でのエタノール改質には Cu/ZnO/Al 2 O 3 触媒が適することを,明らかに している. (7) また,基礎的知見を得る為,触媒層内の温度分布はほぼ均一となる様に管理し,種々の条件,すなわち,いく つかの液空間速度LHSV と反応温度T R に関して,ガス・クロマトグラフによる各組成の濃度やエタノール転化率を明らかに している.…”
Section: 緒 緒 緒 緒言 言 言 言unclassified
See 1 more Smart Citation
“…(1)- (6) しかし,実用改質器設計の際に必要となる実機スケー ルの改質器については,あまり詳細に調べられていない.そこで,著者らは,これまでに,設計規範確立の為の 基礎研究を実施してきた. (7), (8) すなわち,実用的大きさを有する改質器を用い,効率的改質の為の種々の最適反応 条件を調べてきた.その結果,低反応温度でのエタノール改質には Cu/ZnO/Al 2 O 3 触媒が適することを,明らかに している. (7) また,基礎的知見を得る為,触媒層内の温度分布はほぼ均一となる様に管理し,種々の条件,すなわち,いく つかの液空間速度LHSV と反応温度T R に関して,ガス・クロマトグラフによる各組成の濃度やエタノール転化率を明らかに している.…”
Section: 緒 緒 緒 緒言 言 言 言unclassified
“…(7), (8) すなわち,実用的大きさを有する改質器を用い,効率的改質の為の種々の最適反応 条件を調べてきた.その結果,低反応温度でのエタノール改質には Cu/ZnO/Al 2 O 3 触媒が適することを,明らかに している. (7) また,基礎的知見を得る為,触媒層内の温度分布はほぼ均一となる様に管理し,種々の条件,すなわち,いく つかの液空間速度LHSV と反応温度T R に関して,ガス・クロマトグラフによる各組成の濃度やエタノール転化率を明らかに している. (8) 本報では,前報 (7), (8) に引き続き,実用的大きさを有する改質器を用い,効率的改質の為の種々の最適反応条件…”
Section: 緒 緒 緒 緒言 言 言 言unclassified
“…Many researchers have suggested that catalysts containing copper promote dehydrogenation of ethanol to acetaldehyde, while the presence of nickel favors the breaking of carbon-to-carbon bond formation of methane, carbon monoxide and hydrogen. Shinoki et. al.…”
Section: Introductionmentioning
confidence: 99%
“…1 Experimental apparatus. (1) Pump for water, (2) pump for fuel, (3) mixer, (4) vaporisation unit, (5) inner pipe, (6) outer pipe, (7) catalyst, (8) electric heater, (9) gas burner, (10) thermal diffuser, (11) sheathed thermocouple,…”
mentioning
confidence: 99%
“…緒言 現在,化石燃料の大量消費に対する環境保全策,すなわち,窒素酸化物(NO x )や硫黄酸化物(SO x )などによる大気 汚染防止や地球温暖化に対する二酸化炭素(CO 2 )排出削減は, 各界で積極的に取り組まれている. この背景のもと, 環境に優しいエネルギー変換装置の一つとして,燃料電池が注目を集めている.燃料電池反応に必要な水素(H 2 )については,化石燃料起源の炭化水素(C n H m )を燃料として,触媒を用いて水蒸気改質反応させ生成する方法が, 一般的である (1),(2) …”
unclassified